2017
DOI: 10.3390/nu9030286
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of Diet on Treatment Effect from Anti-TNF Drugs in Inflammatory Bowel Disease

Abstract: We wanted to investigate the current knowledge on the impact of diet on anti-TNF response in inflammatory bowel diseases (IBD), to identify dietary factors that warrant further investigations in relation to anti-TNF treatment response, and, finally, to discuss potential strategies for such investigations. PubMed was searched using specified search terms. One small prospective study on diet and anti-TNF treatment in 56 patients with CD found similar remission rates after 56 weeks among 32 patients with good com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 91 publications
(129 reference statements)
0
29
0
1
Order By: Relevance
“…adherent layer, prevents large particles and intact microbes from coming into direct contact with the underlying epithelium; thus, the lower adherent layer is generally free from microbes (63). Low levels of fiber may change the gut microbial metabolism from primarily using microbial derived SCFAs to mucinous carbohydrates as the main energy source, thereby degrading the mucus (64,65). It has been suggested that plant fiber may be important for restoring the mucus layer (63).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…adherent layer, prevents large particles and intact microbes from coming into direct contact with the underlying epithelium; thus, the lower adherent layer is generally free from microbes (63). Low levels of fiber may change the gut microbial metabolism from primarily using microbial derived SCFAs to mucinous carbohydrates as the main energy source, thereby degrading the mucus (64,65). It has been suggested that plant fiber may be important for restoring the mucus layer (63).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that plant fiber may be important for restoring the mucus layer (63). In addition, high intake of meat containing organic sulfur may increase the amount of sulfate for microbially produced hydrogen sulfide (66,67) that may then reduce the disulfide bonds in the mucus network, rendering the mucus layer penetrable to bacteria (65,68,69). Bacteria may then reach the epithelium and activate the TLR-induced gut inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, the attention of investigators was necessarily re-directed towards studying the reasons for the erratic response of IBD to the various anti-TNF antagonists, and one of the main questions asked whether simultaneous treatment of the patient with biologic drugs and a special diet could improve effectiveness. Most of the studies were drawn in CD [52]. Two main designs were used: 1) Investigation of the effects of 9 superimposing an elemental diet; 2) Study of the effects of diet modification in the course of treatment, using a Food Frequency Questionnaire (FFQ).…”
Section: B)mentioning
confidence: 99%
“…In this chain of events, the prime mover is the shortage of fibre, which boosts growth of mucin-degrading strains, such as the various Ruminococci that are found abundant in UC; degradation of mucus would then make available sulphate for degradation by noxious bacteria such as Bilephila Wadsworthi, capable to induce gut membrane ulceration. Large breaches in the mucus shield would allow antigenic luminal contents to be intercepted by TLR sensors, which, responding to bacterial antigenic motifs, can activate the pro-inflammatory chain down to TNF-α production with local and systemic inflammation [52].…”
Section: B)mentioning
confidence: 99%
“…7 Additionally, a westernized lifestyle and environmental impact is associated with increased risk of IBD, which may be linked to changes in the gut microbiome. 8 Accordingly, the prevalence in the West is increasing. 9 Cigarette smoking also affects the risk of IBD and gene-smoking interactions have been identified.…”
Section: Introductionmentioning
confidence: 99%